(untitled) (International Journal of Nursing Education, 2024)
The global elderly population is experiencing a rising prevalence of diabetes mellitus (DM). As a chronic and noncommunicable disease, diabetes requires strict daily self-management, significantly affecting the health-related quality of life (HRQOL). We investigated the relationship between diabetes self-management behaviors and HRQOL in a population of older adults diagnosed with type 2 diabetes mellitus (T2DM). This cross-sectional study was conducted between March 2022 and August 2022 at Phramongkutklao Hospital, Bangkok, Thailand. Participants completed questionnaires measuring sociodemographic factors, we utilized the Diabetes Self-Management Questionnaire (DSMQ) and the Diabetes-39 Questionnaire (D-39) to assess self-management behaviors. Hierarchical linear regression analysis was then employed to investigate the association between diabetes self-management and HRQOL. A total of 252 participants with a mean age of 68.96 years (SD = 6.64) were included. Most participants were aged 60-69 years (57.0%), female (59.9%), married (81.0%), had an undergraduate education (56.7%), and had an income lower than or equal to 40,000 baht (76.6%). Three factors were associated with HRQOL: compliance with cardiovascular disease (β = 0.233, P < 0.001), acute pancreatitis (β = 0.132, P < 0.05), and diabetes self-management (β = -0.376, P < 0.001). Our findings from the final Model 3 analysis revealed a statistically significant positive association between cardiovascular disease (CVD) and HRQOL (standardized β = 0.233, P < 0.001). This indicates that individuals with CVD reported lower HRQOL compared to those without the condition. Similarly, a significant positive association emerged between acute pancreatitis (AP) and HRQOL (standardized β = 0.132, P < 0.05), suggesting a negative impact of this acute illness on HRQOL. Conversely, diabetes self-management demonstrated a significant negative association with HRQOL (standardized β = -0.376, P < 0.001). This implies that better self-management practices among diabetic patients were linked to improved HRQOL. These findings highlight the crucial role of understanding patient perspectives on self-management. Healthcare providers and researchers should prioritize investigating these perspectives to develop and implement interventions that deliver effective diabetes self-management education. Such targeted interventions have the potential to significantly enhance the HRQOL of patients living with diabetes.